MdFRK2-mediated sugar metabolism accelerates cellulose accumulation in apple and poplar - Jing Su; Chunxia Zhang; Lingcheng Zhu; Nanxiang Yang; Jingjing Yang; Baiquan Ma; Fengwang Ma; Mingjun Li (Biotechnology for Biofuels, 2021)
Abstract Background Cellulose is not only a common component in vascular plants, but also has great economic benefits for paper, wood, and industrial products. In addition, its biosynthesis is highly regulated by carbohydrate metabolism and allocation in plant. MdFRK2, which encodes a key fructokinase (FRK) in apple, showed especially high affinity to fructose and regulated carbohydrate metabolism. Results It was observed that overexpression of MdFRK2 in apple decreased sucrose (Suc) and fructose (Fru) with augmented FRK activity in stems, and caused the alterations of many phenotypic traits that include increased cellulose content and an increase in thickness of the phloem region. To further investigate the involved mechanisms, we generated FRK2-OE poplar lines OE#1, OE#4 and OE#9 and discovered (1) that overexpression of MdFRK2 resulted in the huge increased cellulose level by shifting the fructose 6-phosphate or glucose 6-phsophate towards UDPG formation, (2) a direct metabolic pathway for the biosynthesis of cellulose is that increased cleavage of Suc into UDP-glucose (UDPG) for cellulose synthesis via the increased sucrose synthase (SUSY) activity and transcript levels of PtrSUSY1, (3) that the increased FRK activity increases the sink strength overall so there is more carbohydrate available to fuel increased cambial activity and that resulted in more secondary phloem. These results demonstrated that MdFRK2 overexpression would significantly changes the photosynthetic carbon flux from sucrose and hexose to UDPG for increased cellulose synthesis. Conclusions The present data indicated that MdFRK2 overexpression in apple and poplar changes the photosynthetic carbon flux from sucrose and hexose to UDPG for stem cellulose synthesis. A strategy is proposed to increase cellulose production by regulating sugar metabolism as a whole.